Case Report: Cryptocaryonosis in Indian Ocean Oriental Sweetlips (Plectorhinchus vittatus) Fish at the Closed System Quarantine of the Jakarta Aquarium and Safari - Mursalim, drh., M.Kes., Ph.D, Muhammad Fadhlullah; Ramli, Aqidatul Izza; Mustakdir, Zulfikri; Suharto, Rian Hari (Media Kedokteran Hewan, 2024)
Cryptocaryon irritans, known as cryptocaryonosis disease infection in fish, is a significant problem for aquarists because they not only cause the disease but also lead to high mortality in the aquarium population. This case report aims to identify  Cryptocaryon irritans infection in four Indian Ocean oriental sweetlips at the Jakarta Aquarium and Safari. Before they died, a total of four fish showed signs of weakness, scratching, excessive mucus, and pale gills. The diagnosis was confirmed through clinical assessment, physical examination, and microscopic analysis of skin scrape and gill clip samples, which revealed the presence of numerous trophonts (the young immature stages) of C. irritans. These findings underscore the importance of vigilant monitoring and prompt intervention to mitigate the impact of C. irritans, especially on marine aquarium fish populations.